Motivation in tennis - Crespo, M.; Reid, M. M. (British Journal of Sports Medicine, 2007)
Motivation underpins successful tennis performance, representing one of the game`s foremost psychological skills. This paper elaborates on its role in tennis play, and takes an overview of the current state of motivation research applied to tennis. First, the importance of motivation in player and coach performance is explored. The body of evidence pertaining to players` motives for participation and the relevance of goal achievement motivation in tennis is then examined. Finally, the efficacy of motivational climates created by significant others is discussed in light of current practice.